Gaya Hidup Hedonisme dan Lingkungan Non-Fisik serta pengaruhnya terhadap Budaya Organisasi (Studi pada Karyawan Radio Persada Kabupaten Blitar) - Wahyu Prasetyono (Universitas Islam Kadiri, 2020)
Radio Persada as one of the radio located in Blitar District has the function as a seller of information and communication services. The existence of Radio Persada is shaded by the regulation of Blitar Regency. Radio Persada has 20 employees as a power to operate the function of the Radio. In this study researchers took sampling saturated with 20 employees as respondents. The method used is quantitative by using multiple linear regression analysis. The results obtained by using multiple linear analysis mention that 1) Hedonism Lifestyle has no significant effect on Oragnisasi Culture. 2) Non-Physical Environment has a significant effect on Organizational Culture. 3) together that the Lifestyle of Hedonism and Non-Physical Environment has a significant effect on Organizational Culture.